2020
DOI: 10.2174/1573399815666190531083504
|View full text |Cite
|
Sign up to set email alerts
|

Not a Painless Condition: Rheumatological and Musculoskeletal Symptoms in Type 2 Diabetes, and the Implications for Exercise Participation

Abstract: Objectives: People with type 2 diabetes (T2D) are more likely to develop a range of rheumatological and musculoskeletal symptoms (RMS), and experience both chronic and widespread pain, compared with the general population. However, these symptoms are not commonly acknowledged by researchers, which hampers our understanding of the impact on this population. Since exercise is a key lifestyle management strategy for T2D and participation levels are typically low, understanding the potential impact of RMS on exerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 108 publications
0
12
0
Order By: Relevance
“…One factor may be transient increases in pain or other potential adverse events that may occur during exercise training [69,74]. These events are likely underreported in the current literature and the literature base would benefit from reporting adverse events that can accompany exercise training, including, as suggested by Cox and associated (2020), rheumatological and musculoskeletal symptoms [78]. In general, there is a need for more systematic and rigorous investigations that include consistent pain measures to better compare across studies, larger sample sizes, control groups to account for common confounding variables, and comparison studies to help provide specific exercise prescriptions.…”
Section: Discussionmentioning
confidence: 99%
“…One factor may be transient increases in pain or other potential adverse events that may occur during exercise training [69,74]. These events are likely underreported in the current literature and the literature base would benefit from reporting adverse events that can accompany exercise training, including, as suggested by Cox and associated (2020), rheumatological and musculoskeletal symptoms [78]. In general, there is a need for more systematic and rigorous investigations that include consistent pain measures to better compare across studies, larger sample sizes, control groups to account for common confounding variables, and comparison studies to help provide specific exercise prescriptions.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic painful diabetic peripheral neuropathy can cause symptoms that last for years, severely impairing functional activities, and consequently the quality of life ( Cox et al, 2020b ; Daousi et al, 2004 ). The benefits of physical exercise for the prevention and management of type-II diabetes are well established ( Palermi et al, 2020 ), but there is little knowledge on the specific effects of exercise training on chronic pain for this condition ( Cox et al, 2020a ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the interest of HIIT in exercise prescription in the scientific literature is growing. Even if HIIT led to an important decrease in pain in all the selected articles for this review, in some of them no significant difference with MICT were observed ( Cox et al, 2020a ).…”
Section: Discussionmentioning
confidence: 96%
“…Limitations of the study include the small sample size and exploratory investigation of the effects of exercise training on self-reported symptoms. A lack of validated instruments exist to capture the multidimensional and multisite nature of symptoms experienced by people with type 2 diabetes [2]. As widespread chronic pain is common in people with type 2 diabetes, we summed pain intensity scores across nine areas of the body as an index of global pain intensity.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of physical exercise for the prevention and management of type 2 diabetes are well established, including improved glucose control, cardiorespiratory fitness, muscular strength, muscle mass, and body composition [1]. In contrast, there is little knowledge on the specific effects of exercise training on chronic pain in this population [2]. This is despite growing evidence that people with type 2 diabetes are more likely to develop a range of rheumatological and musculoskeletal problems, and experience both widespread and neuropathic pain [3][4][5].…”
Section: Introductionmentioning
confidence: 99%